The Adaptation Pattern in Landed Rental Houses: A Case Study of Gresik Industrial Area - Mutia Sulistiastuti; Dewi Septanti (Journal of Architecture & Environment, 2023)
Contracted houses, or landed rental houses, were developed spontaneously by homeowners as the cheapest alternative for renting houses with flexible contracts. Therefore, landed rental homes are not designed to suit the needs of tenants, and several variations will occur in landed rental homes as a form of adjustment for the owner. Adaptation is significant in the process of building a house. However, given the limited time context in rental housing, the adaptation process is interesting to study more deeply. Gresik is a developing district, and the large number of industries in Gresik has triggered many migrants, most of whom are industrial workers and rent houses on site. This study identifies the adjustment of semi-fixed features and analyzes the adaptation pattern in three types of landed rental houses—40, 50, and 60 m2—using the descriptive-qualitative method. The techniques used here are in-depth interviews, on-the-spot sketches, and observations. From the research that has been done, it was found that each type of landed rental houses has their own adaptation pattern. Generality pattern was found in all the three types, while the flexibility pattern was found in the second and third types.